Diabetic Striatopathy in Pediatric Patient: A Case Report on a Reversible and Acquired Movement Disorder - Maela P. Palisoc; Annfel Jave S. Navarro; Roland Dominic G. Jamora (Acta Neurologica Taiwanica)
Purpose: To present a rare case of diabetic striatopathy (DS) in a child with type 1 diabetes mellitus (DM) with reversible unilateral hemichorea-hemiballismus. Case Report: We report a case of an adolescent girl with uncontrolled type 1 DM who presented with hemichorea-hemiballismus of the right extremities. Cranial magnetic resonance imaging (MRI) showed hyperintense signals on bilateral basal ganglia. There was improvement in hemichorea- hemiballismus as blood glucose levels normalized. Conclusion: A high index of suspicion is required to make a diagnosis of DS in children presenting with abnormal movement disorder and characteristic neuroimaging findings in a background of uncontrolled DM.